Tea Time Numerical Analysis - Brin, Leon; Open Textbook Library (Open Textbook Library, 2016)
This textbook was born of a desire to contribute a viable, free, introductory Numerical Analysis textbook for instructors and students of mathematics. The ultimate goal of Tea Time Numerical Analysis is to be a complete, one-semester, single-pdf, downloadable textbook designed for mathematics classes. Now includes differential equations. Over 350 pages Over 1000 lines of code Over 200 figures Open source
1 Preliminaries -- 2 Root Finding -- 3 Interpolation -- 4 Numerical Calculus -- 5 More Interpolation -- 6 Ordinary Differential Equations
In English.
Description based on print resource
Keywords: Mathematics -- Textbooks